Impact on Ferroelectricity and Band Alignment of Gradually Grown Au on BaTiO3. Issue 7 (1st April 2019) - Popescu, Dana Georgeta; Husanu, Marius Adrian; Chirila, Cristina; Pintilie, Lucian; Teodorescu, Cristian Mihail
Abstract : The competition between interface barrier in the Schottky–Mott limit and polarization driven mechanism is established during gradual formation of metal (Au) – ferroelectric (BaTiO3 ) interface. X‐ray photoelectron spectroscopy provides core level energies and valence band positions in the contact region, to monitor the band alignment from the very first stages of metal deposition on BaTiO3 . The band bending at metal/ferroelectric (FE) interface is extracted from the shift of core levels (Ba 3 d, Ti 2 p ) as a function of the metal thickness. It is shown that the interface band alignment mechanism involves a well‐defined polarization orientation washing out the bending expected from the work function difference. The sudden modification of the binding energies within ferroelectric at the first 2 Å Au indicates that the ferroelectric compensation mechanism triggered by the metal overlayer initiates already at ultrathin top layer, while subsequent growth contributes only at a gradual correction of the potential in the FE. The emerging picture is confirmed in first‐principle calculation indicating the preferences of Au to grow preferentially to different terminated regions and to stabilize distinct ferroelectric polarization. Abstract : The competition between interface barrier in the Schottky–Mott limit and polarization driven mechanism is established for Au–BaTiO3 system. The interface band alignment mechanism involves a well‐defined polarization orientation, surprisingly, washing out the bending extracted from the shift of core levels as a function of the metal thickness and expected from the work function difference.